Persistent HIV‐controllers are more prone to spontaneously clear HCV: a retrospective cohort study. Issue 9 (9th September 2020) - Dominguez‐Molina, Beatriz; Tarancon‐Diez, Laura; Milanés‐Guisado, Yusnelkis; Genebat, Miguel; Resino, Salvador; Rodriguez, Carmen; Gonzalez‐García, Juan; Rallón, Norma; Pernas, Maria; Casado, Concepción; Lopez‐Galíndez, Cecilio; León, Agathe; et al.
Abstract: Introduction: HIV‐controllers have the ability to spontaneously maintain viraemia at low or undetectable levels in the absence of antiretroviral treatment. Furthermore, HIV‐controllers seem to have a superior capacity to spontaneously clear hepatitis C virus (HCV) compared to non HIV‐controllers. Some of these subjects eventually lose HIV‐controller status (transient controllers), whereas some HIV‐controllers show a persistent natural HIV control (persistent controllers). We aimed to analyse whether persistent controllers have superior capacity to spontaneously clear HCV compared to transient controllers. Methods: We recruited HIV‐controllers from January 1981 up to October 2016 with available antibodies to HCV (anti‐HCV) data (n = 744). Factors associated with HIV spontaneous control in relation to HCV status were analysed in persistent and transient HIV‐controllers with anti‐HCV positive (n = 202 and n = 138 respectively) in comparison with 1700 HCV positive non HIV‐controllers recruited from January 1981 up to March 2018, bivariate and multivariate analyses, following a logistic regression model, were applied. In addition, the factors related to the loss and time to lose HIV‐controller status were explored (n = 744) using Log rank test and Kaplan–Meier curves, in this case the multivariate analysis consisted in a Cox regression model. Results: A higher frequency of HCV spontaneous clearance was found in persistent HIV‐controllers (25.5%) compared to non‐controllers (10.2%). After adjusting for potential confounders, as sex, age, HIV transmission risk, CD4 + T‐cell nadir and time of follow‐up, HCV clearance was independently associated with persistent HIV spontaneous control ( p = 0.002; OR (95% CI) = 2.573 (1.428 to 4.633)), but not with transient spontaneous control ( p = 0.119; 1.589 (0.888 to 2.845)). Furthermore, persistent HIV‐controllers were more likely to spontaneously clear the HCV in comparison with transient controllers ( p = 0.027; 0.377 (0.159 to 0.893). Finally, not to lose or lengthen the time of losing this control was independently associated with HCV spontaneous clearance ( p = 0.010; 0.503 (0.297 to 0.850). Conclusions: This study shows an association between spontaneous persistent HIV‐control and HCV spontaneous clearance. The study findings support the idea of preserved immune mechanisms in persistent HIV control implicated in HCV spontaneous clearance. These results highlight persistent HIV‐controllers but not transient controllers as a good model of functional HIV cure.